Vključenost staršev v trenažni in tekmovalni proces mladih športnikov - Kopše, Eva Ivana (Šport (Ljubljana), 2023)
The purpose of this study was to evaluate parents‘ involvement in youth sports and compare it according to age, gender, and sport. 281 young athletes (188 women and 93 men) participated in the study. Parental involvement was measured using the Parental Involvement in Sport Questionnaire (PISQ), which is divided into three sections covering active parental involvement, praise and understanding, and behavioral patterns. Our results show that parental involvement in the training and competition process of young athletes is highest for praise and understanding, moderate for active involvement, and low for parental behavioral patterns. We found no statistically significant gender differences in the level of involvement (p = 0.092 for behavioural patterns, p = 0.236 for frequency of praise and understanding, p = 0.332 for active involvement). Behavioral patterns and frequency of praise did not differ statistically significantly between individual and team sports (p = 0.734; p = 0.318), whereas active parental involvement was statistically significantly higher in individual sports than in team sports (p < 0.05). We also found no correlation between the age of the athletes and parents' behavioural patterns (r = 0.078; p = 0.194), parents' frequency of praise (r = 0.013; p = 0.824) and parents' active involvement (r = 0.078; p = 0.191). The results suggest that parental involvement is appropriate according to the Hellstedt model, but further studies are needed to confirm our findings.
Keywords: mladi športniki; starši; šport; študije; tekmovanja; trenažni proces